TECHNICAL EVALUATION OF CHILDREN AND ADOLESCENTS IN THE "PROJECT OF INITIATION TO FOOTBALL" IN THE CITY OF PATOS - PB. (Fiep Bulletin - online, 2017)
The knowledge of the functions that interact in the training and development process in the school sports preparation is apoint that needed the combination of the scientific and pedagogical parameters with the objective of offering a global income, whichallowed to identify the characteristics and specializations that show the quality and The level of technical skill required for the selectionprocess, which leads to the reflection on the search for different procedures and methods for the current interest in the world of sport,especially in the modality of football. The technical level of the soccer beginners of the educational soccer project in the city of Patos -PB was evaluated. We evaluated 30 young soccer practitioners of the Sub 13 and Sub 17 categories of a soccer project. The studywas developed through the evaluation of technical skills of soccer and it is necessary to evaluate the dribbling, passing, kicking ofathletes, measuring the domain, medium and long pass or throwing, measuring the domain, dribbling and passing, measuring thedomain, Dribbling and kicking, measuring the field, conducting and long pass or throwing, measuring the field and kicking or finishingand therefore assess the technical level of the athletes of children and adolescents beginners of the soccer in the project "EducationalFootball in the city of Patos- PB" The present study was a cross-sectional, descriptive study, and after the tests were performed theathletes were duly scored for evaluation by means of classification, and the data collected were analyzed through descriptivestatistics, and the results were presented Through tables and graphs.